RESEARCH AND ACADEMIC CLUSTER AS A MODEL OF NETWORK COOPERATION - Lyubov V. Ovsienko; Irina V. Zimina; Natalya N. Klintsova; Frank Dr. Müller (Высшее образование в России)
Network cooperation in education between different kinds of educational organizations, enterprises and business partners now becomes the mainstream in educational system of the Russian Federation as an optimizing form of educational process. Research and academic cluster, as a model of network cooperation, enables combining all educational resources, and all members of a cluster can use and develop them.